Antimicrobial effect of Hydroxytyrosol, Hydroxytyrosol Acetate and Hydroxytyrosol Oleate on Staphylococcus Aureus and Staphylococcus Epidermidis. Issue 4 (August 2018) - Ghalandari, Masih; Naghmachi, Mohsen; Oliverio, Manuela; Nardi, Monica; Shirazi, Hamid Reza Ghafarian; Eilami, Owrang
No abstract available